A new parrot taxon from the Yucatán Peninsula, Mexico—its position within genus Amazona based on morphology and molecular phylogeny - Silva, Tony; Guzmán, Antonio; Urantówka, Adam D.; Mackiewicz, Paweł (2017)
Parrots (Psittaciformes) are a diverse group of birds which need urgent protection. However, many taxa from this order have an unresolved status, which makes their conservation difficult. One species-rich parrot genus is Amazona, which is widely distributed in the New World. Here we describe a new Amazona form, which is endemic to the Yucatán Peninsula. This parrot is clearly separable from other Amazona species in eleven morphometric characters as well as call and behavior. The clear differences in these features imply that the parrot most likely represents a new species. In contrast to this, the phylogenetic tree based on mitochondrial markers shows that this parrot groups with strong support within A. albifrons from Central America, which would suggest that it is a subspecies of A. albifrons. However, taken together tree topology tests and morphometric analyses, we can conclude that the new parrot represents a recently evolving species, whose taxonomic status should be further confirmed. This lineage diverged from its closest relative about 120,000 years ago and was subjected to accelerated morphological and behavioral changes like some other representatives of the genus Amazona. Our phylogenies, which are so far the most comprehensive for Amazona taxa enabled us to consider the most feasible scenarios about parrot colonization of the Greater and Lesser Antilles and Central America from South America mainland. The molecular dating of these migrations and diversification rate were correlated with climatic and geological events in the last five million years, giving an interesting insight into Amazon parrot phylogeography and their evolution in general.